Association of XPD Lys751Gln gene polymorphism with susceptibility and clinical outcome of colorectal cancer in Pakistani population: a case–control pharmacogenetic study - Gul, Sumera; Khan, Abad; Raza, Abida; Khan, Ismail; Ehtisham, Shumaila (Genes & genomics, 2020)
Background XPD Lys751Gln polymorphism may modulate inter-individual variation in repair capacity of DNA, which may enhance a person’s susceptibility to develop colorectal cancer (CRC). The analysis of XPD Lys751Gln polymorphism may provide important information for identifying high-risk individuals and for selecting the most appropriate treatment for poor prognostic CRC patients. Objective The overall objective was to find out the association of XPD Lys751Gln gene polymorphism with the risk of having a colorectal cancer and the ultimate clinical outcomes. In this study a total of 300 subjects (CRC and Controls), were genotyped for XPD Lys751Gln. Methods Using PCR–RFLP methods, the association of XPD Lys751Gln gene polymorphism with the risk of having a colorectal cancer was studied. In addition to overall risk assessment, genotyping results were also investigated with respect to the lifestyle risk factors, patients treated with oxaliplatin-based chemotherapy and clinicopathological characteristics. Results The overall correlation between the XPD Lys751Gln genetic variation and the CRC risk was observed to be significant with both the homozygous variant genotype Gln/Gln as well as heterozygous genotype Lys/Gln being associated with the increased risk of CRC. Additional stratified analyses revealed that XPD Lys751Gln variants remarkably increased risk of CRC in males and younger individuals (≤ 50 years), Naswar users (8.09-fold) and high intake of red meat. Conclusions Our findings suggest that the relationship between the XPD Lys751Gln variants and lifestyle factors modulates the risk for CRC in Pakistani population.